PENDIDIKAN KARAKTER DALAM PERSPEKTIF FILSAFAT ILMU - Iqbal Muhammad Syaifulla; Muhammad Nurwahidi; Sudjarwo Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The formation of character in each individual is obtained through formal and informal education and is accepted as early as possible. Character is one of the significant elements that must always be side by side with science. The existence of a nation is closely related to its character. The assessment of a nation cannot be separated from the character of the nation itself. The method used in this study is a systematic literature review. The process of searching for articles was collected by researchers through the Google Scholar database, and Garuda obtained 16 articles as the final result after going through the screening stage. This study aims to examine character education using the perspective of the philosophy of science. This study outcome shows that the students are required to be able to implement character or moral values, so that character education when perceived from the perspective of the philosophy of science acts as an effort to instill intelligence that is projected into the realm of attitude or behavior in a way that is understood, interpreted through the process of thinking and experience.